Isaac newton - Krull Kathleen 1952-2021; Kathleen Krull (New York : Scholastic, 2007)
Isaac Newton was not only briiliant, but secretive, vindictive and obsessive. Here is a portrait of the man, contradictions and all, than places him against the backdrop of seventeenth-century England, a time of plague, the Great Fire of London, and two revolutions.
U
1000